Hubungan Kemampuan Bercerita Guru Terhadap KecerdasanEmosi Anak Kelompok B TK Al Islam 14 Mipitan MojosongoJebres Surakarta Tahun Ajaran 2015/2016 - Erawati, Suci, Drs. Ilham Sunaryo, M.Pd AUD, WILI ASTUTI, S.Pd., M.Pd (2016)
This study aims to identify the relationship between storytelling ability of teacher to the emotional intelligence and the research find out that there is a the relationship storytelling ability of teachers to the children emotional intelligence in kindergarten Al Islam 14 Mipitan Mojosongo Surakarta 2015/2016. This research uses descriptive quantitative research. This research was conducted in kindergarten Al Islam 14 Mipitan Mojosongo Surakarta for kindergarten group B in the academic year 2015-2016. The research sample as many as 30 children from kindergarten and kindergarten Al Islam 14 Mipitan Mojosongo Surakarta. Sampling using simple random sampling. Collecting data using the method of observation and questionnaires. Testing the hypothesis used product moment correlation analysis. Based on the analysis that there is a relationship between the ability to tell the teacher uses props to the emotional intelligence of children in kindergarten Al Islam 14 Mipitan Mojosongo Surakarta 2015/2016. This is evidenced by the results of Pearson correlation r value of 0.505 with a significance of 0.004 <0.01 (p = 0.004; p <0.01) which means there is a significant relationship between the ability to tell the teacher uses props with emotional intelligence of children in kindergarten Al Islam 14 Mipitan Mojosongo Surakarta 2015/2016. Keywords Child emotional intelligence, teacher ability to tell a story.